Berczeli Anzelm Károlyhoz - Várkonyi Zoltán (Fond 380 Berczeli Anzelm Károly írói hagyatéka, 1975)
Fond 380 Berczeli Anzelm Károly írói hagyatéka > Berczeli Anzelm Károly levelezése > Berczeli Anzelm Károlyhoz írt levelek